2022
DOI: 10.3390/soc12060178
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Competence in Healthcare and Healthcare Education

Abstract: Cultural competence in healthcare has been defined in many ways; however, it generally refers to knowledge of social and cultural factors that influence illness and related behaviour, and actions taken to provide the best of quality care considering each patient’s background [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Having explained the rationale and need for this systematic review, our objective was to thoroughly and systematically search, retrieve, and review all Delphi studies that focused on the cultural competencies needed for professionals in the healthcare and allied healthcare sectors. We approached cultural competence in its broadest sense, on par with Constantinou et al's [20] suggestion that cultural competence should be an umbrella term because "culture" is difficult to measure, as it encompasses anything that human beings have created by living in societies [21]. On this basis, in addition to cultural competence, we aimed to search other related terms such as diversity, cultural humility, structural competence, cultural sensitivity, cultural awareness, and intercultural communication [20].…”
Section: Objective and Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having explained the rationale and need for this systematic review, our objective was to thoroughly and systematically search, retrieve, and review all Delphi studies that focused on the cultural competencies needed for professionals in the healthcare and allied healthcare sectors. We approached cultural competence in its broadest sense, on par with Constantinou et al's [20] suggestion that cultural competence should be an umbrella term because "culture" is difficult to measure, as it encompasses anything that human beings have created by living in societies [21]. On this basis, in addition to cultural competence, we aimed to search other related terms such as diversity, cultural humility, structural competence, cultural sensitivity, cultural awareness, and intercultural communication [20].…”
Section: Objective and Research Questionmentioning
confidence: 99%
“…We approached cultural competence in its broadest sense, on par with Constantinou et al's [20] suggestion that cultural competence should be an umbrella term because "culture" is difficult to measure, as it encompasses anything that human beings have created by living in societies [21]. On this basis, in addition to cultural competence, we aimed to search other related terms such as diversity, cultural humility, structural competence, cultural sensitivity, cultural awareness, and intercultural communication [20].…”
Section: Objective and Research Questionmentioning
confidence: 99%
“…Cultural humility encompasses a process of continuous self-evaluation and reflection for healthcare professionals to not only better understand themselves, but also their patients, by being non-judgmental and more open to learn from others. The problem with structural competence is that structures are cultural products, while intercultural communication is missing [23]. By the same token, cultural humility focuses largely on self-reflection and development, missing the importance of social structures and intercultural communication [23].…”
Section: Challenges With the Use Of Cultural Competence And The Need ...mentioning
confidence: 99%
“…The problem with structural competence is that structures are cultural products, while intercultural communication is missing [23]. By the same token, cultural humility focuses largely on self-reflection and development, missing the importance of social structures and intercultural communication [23]. Constantinou et al [23] suggested that cultural competence was still very useful because it constituted a holistic approach and encompassed all necessary elements, from intercultural communication to structures, humility, diversity, etc.…”
Section: Challenges With the Use Of Cultural Competence And The Need ...mentioning
confidence: 99%
See 1 more Smart Citation